Multiple Halogenation of Aliphatic C−H Bonds within the Hofmann–Löffler Manifold. Issue 65 (30th October 2018) - Del Castillo, Estefanía; Martínez, Mario D.; Bosnidou, Alexandra E.; Duhamel, Thomas; O'Broin, Calvin Q.; Zhang, Hongwei; Escudero‐Adán, Eduardo C.; Martínez‐Belmonte, Marta; Muñiz, Kilian
Abstract: An innovative approach to position‐selective polyhalogenation of aliphatic hydrocarbon bonds is presented. The reaction proceeded within the Hofmann‐Löffler manifold with amidyl radicals as the sole mediators to induce selective 1, 5‐ and 1, 6‐hydrogen‐atom transfer followed by halogenation. Multiple halogenation events of up to four innate C−H bond functionalizations were accomplished. The broad applicability of this new entry into polyhalogenation and the resulting synthetic possibilities were demonstrated for a total of 27 different examples including mixed halogenations. Abstract : More than one at a time ! Multiple site‐selective C−H halogenation events can be accomplished as an innovative variant of the classic Hofmann–Löffler reaction by using halogenated hydantoins as oxidant and halide source. The reaction scope includes cyclic and linear hydrocarbons, as well as vicinal and geminal halogenation.